RETRACTED: Meta analysis of clinical prognosis of radiofrequency ablation versus partial nephrectomy in the treatment of early renal cell carcinoma - Qu, Hongchen; Wang, Kai; Hu, Bin (Frontiers in Oncology, 2023)
Objective: To systematically review the differences between radiofrequency ablation and partial nephrectomy in patients with early-stage renal cell carcinoma, and to provide evidence-based medical evidence for the choice of surgery for patients with early-stage renal cell carcinoma. Methods: According to the search strategy recommended by the Cochrane Collaboration, Chinese databases such as CNKI, VIP Chinese Science and Technology Periodicals Database (VIP), and Wanfang Full-text Database were searched with Chinese search terms. And PubMed and MEDLINE as databases for English literature retrieval. Retrieve the relevant literature on renal cell carcinoma surgical methods published before May 2022, and further screen radiofrequency ablation and partial nephrectomy in patients with renal cell carcinoma The relevant literature on the application is analyzed. RevMan5.3 software was used for heterogeneity test and combined statistical analysis, sensitivity analysis, and subgroup analysis. Analysis, and draw forest plot, using Stata software Begger quantitative assessment of publication bias. Results: A total of 11 articles were involved, including 2958 patients. According to the Jadad scale, 2 articles were of low quality, and the remaining 9 articles were of high quality. Results of this study demonstrates the advantages of radiofrequency ablation in early-stage renal cell carcinoma. The results of this meta-analysis showed that compared with partial nephrectomy, there was significant difference in the 5-year overall survival rate between radiofrequency ablation and partial nephrectomy and there was a statistically significant difference between the two surgical methods in the 5-year relapse free survival rate of early renal cell carcinoma. Conclusions: 1. Compared with partial nephrectomy, the 5-year relapse-free survival rate，the 5-year cancer specific survival rate and the overall 5-year survival rate were higher in the radiofrequency ablation group. 2. Compared with partial nephrectomy, there was no significant difference in the postoperative local tumor recurrence rate of radiofrequency ablation. 3. Compared with partial resection, radiofrequency ablation is more beneficial to patients with renal cell carcinoma.